Glucagon-like peptide-2-loaded microspheres as treatment for ulcerative colitis in the murine model. (18th August 2015) - Wu, Jie; Qi, Keke; Xu, Ziwei; Wan, Jin
Abstract: Glucagon-like peptide-2 (GLP-2) is an intestinal hormone that promotes intestinal growth, but the rapid degradation by dipeptidyl peptidase-IV limits its applications. PLGA microsphere is a well-developed drug delivery system, while seldom been studied as a solution for prolonging in vivo effects of GLP-2. In this study, we encapsulated porcine GLP-2 (pGLP-2) into microspheres and investigated its therapeutic effects in dextran sulfate sodium (DSS)-treated mice. pGLP-2 microspheres showed 20.36% in initial burst and constant release for at least 9 d. In the DSS-treated mice, a single injection of GLP-2 microspheres significantly increased the body weight, colonic length, small intestinal weight and mRNA expression of Occludin, decreased the colonic damage score, mRNA expression of IL-6, IL-10, TNF-α and IFN-γ. In conclusion, pGLP-2 microspheres were resistant to degradation and decreased the severity of DSS-induced ulcerative colitis which suggested that GLP-2-loaded microspheres could be a proper candidate for the treatment of ulcerative colitis.